The Effect of Dhikr Relaxation Techniques on Stress Level in Hypertension Patients Literature Review - Taufik Septiawan; Muhammad Tarmidzi Idris (Global Health Science Group, 2021)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolik blood pressure of more than 90 mmHg. People with hypertension is easy to have stress. If people with hypertension feel stress so long, it will be causing complications. So to manage stress, relaxation techniques can be made, one of which is spiritual relaxation, namely dhikr relaxation. The purpose of the study is to determine the effect of dhikr relaxation techniques on stress level in hypertension sufferers. The purpose of this study was to determine the effect of dhikr relaxation techniques on stress levels in patients with hypertension. The purpose of the study is to determine the effect of dhikr relaxation techniques on stress level in hypertension sufferers. This research used literature review design with traditional review. As for totally of journal reviewed is 15 journal contain of 5th national journal and 10th international journal. The results of hypothesis testing in 15 journals with any test of hypothesis we got result if there is a significant effect of spiritual relaxation techniques : dzikr on stress level in hypertension sufferers. Dhikr relaxation techniques decrease stress level, the stress level from high to moderate and the level of stressmoderate become light after doing dhikr relaxation techniques. Th result of journal analysys could be suggest to additional courses on complementary therapy and add knowledge to nursing student about dhikr techniques and also could be applied as nursing implementation.